Inactivation kinetics of horseradish peroxidase (HRP) by hydrogen peroxide - Diego Morales-Urrea; Alex López-Córdoba; Edgardo M. Contreras (Scientific Reports, 2023)
Abstract In recent years, the peroxidase enzymes have generated wide interest in several industrial processes, such as wastewater treatments, food processing, pharmaceuticals, and the production of fine chemicals. However, the low stability of the peroxidases in the presence of hydrogen peroxide (H2O2) has limited its commercial use. In the present work, the effect of H2O2 on the inactivation of horseradish peroxidase (HRP) was evaluated. Three states of HRP (E0, E2, and E3) were identified. While in the absence of H2O2, the resting state E0 was observed, in the presence of low and high concentrations of H2O2, E2, and E3 were found, respectively. The results showed that HRP catalyzed the H2O2 decomposition, forming the species Ex, which was catalytically inactive. Results suggest that this loss of enzymatic activity is an intrinsic characteristic of the studied HRP. A model from a modified version of the Dunford mechanism of peroxidases was developed, which was validated against experimental data and findings reported by the literature.